(untitled) (Research, Society and Development, 2022)
Objective: to build and validate educational technology on the concept, treatments and risk factors and essential care for people with colorectal malignancy and their families. Methods: methodological study in three stages: educational technology developed, using the theoretical-methodological model of Doak, Doak and Root, content and appearance validation by the content validity coefficient. The Delphi technique was applied in two rounds (Delphi I [12 judges]/Delphi II [11 judges]), and a pilot test was carried out with eight individuals with colorectal malignancy and their families. Results: the educational technology “Educational booklet for people with colorectal cancer: let’s talk about colorectal cancer?” contemplated the concept of colorectal cancer, risk factors, treatment options, living with an intestinal ostomy and its care, when seeking health care. It presented a global content validity coefficient (Delphi II) equal to 0.98. Conclusion: the educational technology presented content and appearance validity for health education for people with colorectal malignancy and their families.